2003
DOI: 10.1128/jvi.77.20.11212-11219.2003
|View full text |Cite
|
Sign up to set email alerts
|

Productive Infection Maintains a Dynamic Steady State of Residual Viremia in Human Immunodeficiency Virus Type 1-Infected Persons Treated with Suppressive Antiretroviral Therapy for Five Years

Abstract: To provide insight into the dynamics and source of residual viremia in human immunodeficiency virus (HIV) patients successfully treated with antiretroviral therapy, 14 intensely monitored patients treated with indinavir and efavirenz sustaining HIV RNA at <50 copies/ml for >5 years were studied. Abacavir was added to the regimen of eight patients at year 5. After the first 9 months of therapy, HIV RNA levels had reached a plateau ("residual viremia") that persisted for over 5 years. Levels of residual viremia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
133
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 50 publications
11
133
4
Order By: Relevance
“…The same results were obtained with resting T cells from PBMCs of viremic patients (14,27,33,34). Resistance of HIV-1 replication to antiretroviral drugs in resting memory CD4 ϩ T cells of infected individuals highlights an urgent need to search for new HIV therapies.…”
Section: Cd62lsupporting
confidence: 67%
See 1 more Smart Citation
“…The same results were obtained with resting T cells from PBMCs of viremic patients (14,27,33,34). Resistance of HIV-1 replication to antiretroviral drugs in resting memory CD4 ϩ T cells of infected individuals highlights an urgent need to search for new HIV therapies.…”
Section: Cd62lsupporting
confidence: 67%
“…Later, in many cases, CXCR4-utilizing variants (X4 variants) evolve and are associated with depletion of CD4 ϩ T cells and with a rapid progression to AIDS. Recent studies have clearly established that infection with HIV-1 predominantly occurs in CD4 ϩ memory T cells (8,14,27,29,47,51,57,67). Memory cells comprise several subsets defined by differential expression of CD45RA, CD45RO, homing receptors, and activation markers (16,35,41,52).…”
mentioning
confidence: 99%
“…These include the persistence of replication-competent virus (2-4), unintegrated proviral DNA, both linear (2) and circularized (13,14), and cell-associated HIV RNA (6,7,11,15,16). In addition, other studies have demonstrated that intensification of conventional antiviral regimens in patients who remained aviremic accelerated the decay of the latent HIV reservoir in the resting CD4 + T cell compartment (12) and further suppressed plasma viremia to well below the limit of detection (3.2-23 copies of HIV RNA per ml) (17). These findings suggest that low levels of ongoing HIV replication continue to persist and may contribute to the longevity of the latent viral reservoir by continually fueling new rounds of infection in resting CD4 + T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that a pool of latently infected cells is established during the primary phase of HIV infection (Bonhoeffer et al, 1997;Grossman et al, 1998;Havlir et al, 2003;Lafeuillade et al, 2000;Muller et al, 2002). These cells are infected cells in a resting state and can be activated after a long time of dormancy to produce infectious virus particles.…”
Section: Modeling Latently Infected Cellsmentioning
confidence: 99%